"Islands in the stream": toward a new history of the large islands of the Byzantine Mediterranean in the early Middle Ages ca.600–ca.800. Issue 2 (3rd July 2018) - Zavagno, Luca
Abstract : Byzantine historiography has often regarded the large Mediterranean islands (Cyprus, Crete, Sardinia, Malta and the Balearics) as mere peripheral additions to the Byzantine heartland – defined as the coupling of two different geographical zones: the Anatolian plateau and the Aegean. As a result, Byzantinists seem not to have fully moved away from an interpretative framework which regards islands as either strategic military bulwarks along the Arab-Byzantine Mediterranean frontier, or as neglected marginal outposts soon to be lost forever. A partial exception to this historiographical periphericity of large islands is represented by Sicily, because of its relevance as a secure source for grain after the disruption of the Egyptian tax-spine in the 640s. In fact, by comparing material and archaeological evidence with literary and documentary sources, an alternative interpretation of the political, economic and cultural role played by large islands will be proposed, this by pairing two main themes: the first revolving around the economics of insular societies; and the second stressing the importance of islands as connective hubs with peculiar local political, social and cultural structures which remained within the Byzantine sphere of influence for longer than previously thought. This approach allows us to tip the unbalanced dialogue between margins and metropolis by pointing to a relatively higher welfare of the insular world as stemming from the uninterrupted, although diminished, "connective" role the abovementioned islands played within the Mediterranean shipping routes linking the eastern and western basin of the Mediterranean. In this light, the adaptive strategies of insular administrative structures as influenced by the political or military difficulties of the hour, as well as the urban socio-political and economic structures on some of the abovementioned Byzantine islands, will also be documented. This is because the construction of urban models, settlement strategies and infrastructures – although often based on diverse political and administrative policies – nevertheless point to the presence of common, cross-cultural insular developments such as: the role of members of urban-oriented aristocracies as cultural brokers; the creation of commercial and artisanal facilities; the construction or restoration of religious buildings as foci of settlement and regional as well as interregional pilgrimage; the resilience of local elites as catalysts of patronage; and the persistence of levels of demand often based upon regular if not frequent regional and sub-regional trans-maritime contacts.